Analysis of the model OPM3® application and results for health area - Luis Augusto dos Santos; Heimar de Fátima Marin (O Mundo da Saúde, 2011)
This research sought to analyze if a questionnaire model created by an international community of project management is applicable to health organizations. The model OPM3® (Organizational Project Management Maturity Model) was created in order that organizations of any area or size can identify the presence or absence of good management practices. The aim of applying this model is to always evaluate the organization and not the interviewee. In this paper, one presents the results of employing this model in an organization that has information technology products and services applied to health area. This study verified that the model is rapidly applicable and that the analyzed organization has an expressive number of good practices.